Shortened therapy of eight weeks with paritaprevir/ritonavir/ombitasvir and dasabuvir is highly effective in people with recent HCV genotype 1 infection. - Martinello,M; Bhagani,S; Gane,E; Orkin,C; Cooke,G; Dore,GJ; Petoumenos,K; Applegate,TL; Tu,E; Marks,P; Pagani,N; Grebely,J; et al. (J Viral Hepat, 2018)
Paritaprevir/ritonavir/ombitasvir and dasabuvir with or without ribavirin for 12 weeks is approved for treatment of chronic HCV genotype 1 infection. This study assessed the efficacy of shortened duration paritaprevir/ritonavir/ombitasvir and dasabuvir with or without ribavirin for eight weeks among people with recent HCV infection. In this open-label single-arm trial conducted in Australia, England and New Zealand, adults with recent HCV (duration of infection <12 months) received paritaprevir/ritonavir/ombitasvir and dasabuvir (with weight-based ribavirin for genotype 1a and 1, no subtype) for eight weeks. The primary endpoint was sustained virologic response at 12 weeks post-treatment (SVR12) in the intention-to treat (ITT) population. Thirty people (median age 38 years, male 93%) commenced treatment (with ribavirin, 97%), of whom 77% (n=23) were HIV-positive, 93% (n=28) had genotype 1a infection and 53% (n=16) had ever injected drugs. Median maximum ALT in the preceding 12 months was 433 IU/L (IQR 321, 1012). Acute clinical hepatitis with ALT>10xULN was documented in 83% (n=25); one participant (3%) had jaundice. At baseline, median estimated duration of infection was 30 weeks (range 11, 51) and median HCV RNA was 5.7 log10 IU/mL (range 2.7, 7.3). SVR12 was achieved in 97% (29/30; early discontinuation at week 2, n=1; per-protocol 100%, 29/29). No relapse or reinfection was observed. In conclusion, Paritaprevir/ritonavir/ombitasvir and dasabuvir (with ribavirin) for eight weeks was highly effective among HIV-positive and HIV-negative individuals with recent HCV infection. This data supports the use of this shortened duration direct-acting antiviral regimen in this population. This article is protected by copyright. All rights reserved.